Mycoplasma genitalium: a review. (June 2014) - Daley, GM; Russell, DB; Tabrizi, SN; McBride, J
Mycoplasma genitalium (M. genitalium) was first isolated from the urethral swabs of two symptomatic men with urethritis in 1980. Published prevalence rates vary greatly between populations studied. A number of urogenital conditions have been ascribed to M. genitalium, which is recognised to cause a sexually transmitted infection. The association of M. genitalium with non-specific urethritis is now well established, but the evidence supporting its role in both male and female infertility remains inconclusive. Laboratory methods are challenging and there is a lack of test standardisation. The recommended treatment of the infection is azithromycin as a single 1 gm dose. However, in recent years macrolide resistance has been observed. More studies are required to establish the clinical importance of M. genitalium in urogenital conditions, particularly infertility, and to establish the role for screening and treatment in high-risk populations.